Socio-Economic Characteristics of Women Entrepreneurs in Botswana - Sibanda, Khulekani; sangodoyin, Oluranti Olukemi (International Journal of Business, Management and Economics, 2024)
The present study offers a comprehensive examination of the socio-economic attributes of female entrepreneurs in Botswana, specifically emphasizing the convergence of demographic profiles, educational backgrounds, and entrepreneurial performance. Employing a mixed-methods approach that combines quantitative and qualitative research, the study rigorously analyses the elements influencing entrepreneurial outcomes for women in the region. The findings emphasize a robust positive association between increased levels of education and the achievement of business success. Specifically, women with higher education qualifications exhibit better business results in revenue growth, market expansion, and operational profitability. Nevertheless, the research also reveals enduring obstacles female entrepreneurs encounter, namely in obtaining financial access, managing socio-cultural limitations, and harmonizing family responsibilities with business requirements. The results emphasize the necessity of implementing focused policy measures, educational changes, and support structures that specifically tackle the distinct obstacles that women encounter in entrepreneurship.